Harnessing the Single-Session Intervention approach to promote scalable implementation of evidence-based practices in healthcare - Schleider, Jessica L.; Beidas, Rinad S. (Frontiers in Health Services, 2022)
Effective implementation of evidence-based practices often involves multi-level strategies targeting individual-, organizational-, and system-level determinants of change. Although these multi-level implementation approaches can successfully facilitate EBP uptake, they tend to be complex and resource intensive. Accordingly, there is a need for theory-driven, generalizable approaches that can enhance efficiency, cost-effectiveness, and scalability of existing implementation approaches. We propose the Single-Session Intervention approach as an unexplored path to developing low-cost and scalable implementation strategies, especially those targeting individual-level behavior change. We argue that single-session strategies (S3) for implementation, which can simultaneously target myriad barriers to individual behavior change, may promote clinicians’ EBP uptake and sustainment in a manner that is low-resource and scalable. We first overview the evidence-base supporting the Single-Session Intervention approach for patient-level outcomes; situate this approach within the implementation science literature by outlining its intersections with a leading framework, the Theoretical Domains Framework (TDF), as an exemplar; and illustrate how the TDF might directly inform the design and evaluation of single-session strategies for EBP implementation. Overall, single-session strategies (S3) for implementation reflect a promising but yet-to-be-tested means of streamlining and scaling individual-level behavior change efforts in healthcare settings. Future partnered research is needed to gauge the potential of this approach across diverse clinical and community contexts.